2021
DOI: 10.1145/3449201
|View full text |Cite
|
Sign up to set email alerts
|

Sensemaking and Coping After Pregnancy Loss

Abstract: Emotional validation describes when one believes that their activities, emotions, beliefs, or other reactions are relevant and meaningful given the circumstance. When people experience distressing, stigmatizing life events, their state of emotional validation and thus their perceived sense of normalcy is often disrupted. Online spaces offer opportunities for coping, managing, and making sense of distress and stigma. In this paper, we focus on pregnancy loss as the context of inquiry and as an important example… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(13 citation statements)
references
References 90 publications
3
10
0
Order By: Relevance
“…Our participants either began or continued their general PCOS search by accessing evidence-based medical websites. Supporting prior research (e.g., [ 36 , 42 , 43 , 58 ]), we found our participants utilising both evidence-based medical information and experiential information through online social support networks, to better understand their condition. Where experiential information was thought to be unreliable, medical evidence-based information was used to check its veracity.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Our participants either began or continued their general PCOS search by accessing evidence-based medical websites. Supporting prior research (e.g., [ 36 , 42 , 43 , 58 ]), we found our participants utilising both evidence-based medical information and experiential information through online social support networks, to better understand their condition. Where experiential information was thought to be unreliable, medical evidence-based information was used to check its veracity.…”
Section: Discussionsupporting
confidence: 86%
“…This study extends prior work on women’s information-seeking relating to PCOS [ 28 , 30 ], their need to establish what is normal for them [ 57 ], and the broader literature on health information-seeking, sense-making and finding a “new normal” based on information-seeking [ 36 – 41 , 43 , 44 , 58 , 59 ]. Working at the intersection of these three themes, this study has identified health information-seeking and sense-making behaviours being applied across a spectrum for PCOS.…”
Section: Discussionsupporting
confidence: 62%
“…In the context of virtual communities and pregnancy loss, previous research (Andalibi & Garcia, 2021) has shown that individuals turn to online spaces to process their grief experiences and connect with others who can relate to their situation. These virtual communities have been found to facilitate a collaborative process of sensemaking, allowing individuals to collectively make sense of their situation (Mamykina et al, 2015; Young & Miller, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…These virtual communities have been found to facilitate a collaborative process of sensemaking, allowing individuals to collectively make sense of their situation (Mamykina et al, 2015; Young & Miller, 2019). For individuals coping with pregnancy loss, virtual communities offer valuable support and empathy when in‐person support may be limited or inaccessible (Andalibi & Garcia, 2021). However, it remains unclear how these findings extend to pregnant individuals coping with physical symptoms induced by pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…Online support groups are formed or facilitated through digital platforms, which provide a sense of space, shared practice, shared resources and support, shared identities, and interpersonal relationships [ 1 ]. Recent research points at different ways in which stigmatized individuals use digital platforms to actively cope with social stigma [ 2 , 3 , 4 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%